Structural Modeling of Binge Eating Based on Self-Compassion and Impulsivity with the Mediating Role of Emotion Regulation in Male Students with Obesity - Hataminia, Saman; Imankhah, Reza; Nakhaei, Somayeh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to model binge eating behavior in obese male university students based on self-compassion and impulsivity, with emotion regulation serving as a mediating variable. Methods and Materials: The research employed a descriptive-correlational design using structural equation modeling (SEM). The sample consisted of 225 obese male students from Islamic Azad University in Zabol, selected through simple random sampling. Data were collected using four validated self-report instruments: the Binge Eating Scale (Stice et al., 2008), Self-Compassion Scale (Reis et al., 2011), Barratt Impulsiveness Scale (BIS-11), and the Difficulties in Emotion Regulation Scale (DERS; Gratz, 2004). Reliability and validity indices for all instruments were confirmed. Data analysis was performed using SPSS-27 and SmartPLS-3.3. Findings: The results demonstrated that self-compassion significantly predicted lower levels of binge eating (β = -0.81, t = 10.33, p < 0.001), while impulsivity significantly predicted higher binge eating (β = 0.29, t = 3.05, p < 0.01). Self-compassion also significantly predicted better emotion regulation (β = -0.59, t = 6.76, p < 0.001), whereas impulsivity predicted poorer emotion regulation (β = -0.31, t = 3.54, p < 0.001). Emotion regulation significantly mediated the relationship between self-compassion and binge eating (Z = 9.03, p < 0.001), as well as between impulsivity and binge eating (Z = 4.71, p < 0.001). The structural model showed a good overall fit, supporting the hypothesized pathways. Conclusion: The findings highlight the critical role of self-compassion and impulsivity in predicting binge eating behaviors among obese male students, with emotion regulation serving as a key mediating process. Enhancing self-compassion and emotional regulation capacities while addressing impulsive tendencies may reduce maladaptive eating behaviors in this population.